2021
DOI: 10.31130/jst-ud2021-439
|View full text |Cite
|
Sign up to set email alerts
|

High efficient removal of phosphate in aqueous solution by eco-friendly materials

Abstract: The efficiency of phosphate removal in aqueous solution by CaO, Ca(OH)2 and CaCO3 has been studied in this work. Batch of experiments conducted with the initial phosphate concentrations from 5 to 1000 ppm have shown that CaCO3 could be applied for phosphate removal at low concentration with the maximum phosphate removal capacity at 4.0 mg/g. In contrast, the highest phosphate removal capacity of CaO and Ca(OH)2 was 287.36 mg/g and 235.21 mg/g at initial concentration of 500 ppm, and phosphate removal rate was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In previous work, the phosphate removal by using CaO and Ca(OH)2 was tested at initial phosphate concentrations from 5 to 1000 ppm [17]. The results showed that the phosphate removal efficiency reached 85% and 95% at the initial phosphate concentration of 5 ppm by using CaO and Ca(OH)2, respectively.…”
Section: Effect Of Alginic Acid and Nahco3 As Flocculants On Phosphat...mentioning
confidence: 99%
See 1 more Smart Citation
“…In previous work, the phosphate removal by using CaO and Ca(OH)2 was tested at initial phosphate concentrations from 5 to 1000 ppm [17]. The results showed that the phosphate removal efficiency reached 85% and 95% at the initial phosphate concentration of 5 ppm by using CaO and Ca(OH)2, respectively.…”
Section: Effect Of Alginic Acid and Nahco3 As Flocculants On Phosphat...mentioning
confidence: 99%
“…This value made up at 287.36 mg/g and 235.21 mg/g, respectively. Moreover, the product after phosphate treatment can be used as phosphate fertilizer for plants in acid crops [17]. Nevertheless, separation of the precipitate by filtration method (2.7 μm filter paper) seems not to be effective in the sample of initial phosphate concentration at 50 and 1000 ppm.…”
Section: Introductionmentioning
confidence: 99%